Historical bias in palaeontological collections: Stylophora (Echinodermata) as a case study - Pauline Guenser; Khadija El Hariri; Nour-Eddine Jalil; Bertrand Lefebvre (Swiss Journal of Palaeontology)
Abstract Scientific colonialism (sensu Galtung, 1967) has grown in interest for the last decades in all scientific disciplines, including Palaeontology. In particular, Raja et al. (2022) showed that the Paleobiology Database (PBDB) was mostly based on research investigations from and/or in higher-income countries (i.e., the Global North). This scientific practice, better known as “parachute science”, often implies a transfer of material from their country of origin (in the Global South) to another country of collection (in the Global North). We show that this global pattern can also be observed at a lower taxonomic scale by focusing on Stylophora, an extinct class of echinoderms. Based on a database gathering the 129 stylophoran holotypes including information of their year of description, country of origin, country of collection and author affiliation, we show comparable results to those of Raja et al. (2022). Indeed, 85% of stylophoran species originated from the Global North. Transferred material represents 17% of the holotypes and none of the corresponding publications included local collaboration. We detail the most highlighting example of parachute science, the duo Morocco-France, to understand the consequences of the colonial history between these two countries in the scientific practice of French researchers in Morocco, as well as the solution brought by Moroccan researchers and government. These results, while not surprising, mean that scientific colonialism is indeed observed not only in global databases, but also in our daily work. Researchers from the Global North then can act to decolonize their problematic practice to rebalance knowledge producing to build a true Global Research Community.